2016
DOI: 10.4236/jep.2016.73030
|View full text |Cite
|
Sign up to set email alerts
|

Toys, Décor, and More: Evidence of Hazardous Electronic Waste Recycled into New Consumer Products

Abstract: Hazardous chemicals used in electronic and electrical consumer products can re-enter commerce when these products are recycled. The objectives of this study were to 1) identify the possible sources of unexpected chemicals and elements in consumer products, including the use of recycled E-waste plastics and 2) demonstrate bromine detection with nondestructive spectroscopy as an indicator of brominated flame retardants contaminating new products via recycled waste streams. More than 1500 consumer products of div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…BFRs through the dilution of WEEE plastics is a widespread and pervasive issue cross the sector. This assertion is supported by recent studies reporting the total Br content in a range of consumer goods available in the US (Miller et al, 2016) and specific BFRs in a smaller number of consumer products purchased in the EU (Samsonek and Puype, 2013;Ionas et al, 2014;Leslie et al, 2016), Australia (Gallen et al, 2014) and…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…BFRs through the dilution of WEEE plastics is a widespread and pervasive issue cross the sector. This assertion is supported by recent studies reporting the total Br content in a range of consumer goods available in the US (Miller et al, 2016) and specific BFRs in a smaller number of consumer products purchased in the EU (Samsonek and Puype, 2013;Ionas et al, 2014;Leslie et al, 2016), Australia (Gallen et al, 2014) and…”
Section: Discussionmentioning
confidence: 58%
“…Despite attempts to 'close the loop' on harmful BFRs, they have recently been detected in a variety of consumer products that do not require flame retardancy or at concentrations insufficient to provide fire protection, including children's toys (Ionas et al, 2015), kitchen utensils (Samsonek and Puype, 2013), beaded garlands (Miller et al, 2016) and flooring products (Vojta et al, 2017). Thus, in many cases, recycled plastics from WEEE appear to have been used, in whole or in part, to manufacture contemporary electrical and non-electrical products that may not themselves be compliant.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature is reporting the occurrence of BFRs in a range of products where they are neither needed nor expected and present an unnecessary hazard to the consumer. For instance, Miller et al (2016) used XRF to demonstrate the widespread occurrence of Br in plastic consumer goods that had been newly purchased on the US market, with mass spectrometry performed on black necklaces and garlands confirming the presence of several restricted BFRs. Samsonek and Puype (2013) and Kuang et al (2018) detected various restricted BFRs in black thermos cups purchased in the EU and in black kitchen utensils purchased in the UK, respectively, while Chen et al (2009) found several BFRs in toys bought on the Chinese market, including PBBs that had never been produced in the country.…”
Section: Additives In Non-eee Plastics and Evidence For The Recyclingmentioning
confidence: 99%
“…This is due to the need for such methods as recently BFRs have been detected in many consumer goods like toys, plastic FCMs, VHS and polymer-based necklaces (Hirai et al 2007;Miller et al 2016;Guzzonato et al 2016a). We would like to bring this appearance of WEEE in plastic FCMs and their constituents into an actual perspective, therefore as introduction an overview of relevant available literature and findings.…”
Section: Introductionmentioning
confidence: 99%
“…We describe as well the measurement of REEs where combinations of cerium (Ce), dysprosium (Dy), lanthanum (La), neodymium (Nd), praseodymium (Pr) and yttrium (Y) were detected in four of the seven BFR-positive samples. Additionally, the polymer purity was investigated where in all cases foreign polymer fractions were BTBPE, decaBDE, DBDPE, TBBPA, HBCD, 2,4,6-tribromophenol Bromine screening by high-definition (HD) X-ray fluorescence spectrometry (XRF) followed by gas chromatography-mass spectrometry (GC-MS) or liquid chromatography-tandem mass spectrometry (LC-MS/MS) Miller et al (2016) DecaBDE XRF spectroscopy followed by direct insertion probe magnetic sector high-resolution mass spectrometry (HRMS) Guzzonato et al (2016a) PBDEs, PBBs, HBCD, TBBPA, BTBPE, 2,4,6-tribromophenol, TBBPA derivates Laser ablation inductively coupled plasma spectrometry-mass spectrometry (LA-ICP-MS), hand-held XRF spectroscopy followed by thermal desorption GC-MS Guzzonato et al (2016b) PBDEs, TBBPA and TBPE with additional information on Br, P, Cl, Pb, Hg, Cd and Sb XRF spectroscopic screening followed by gas chromatography electron capture detection (GC-ECD) or HRMS in extracts Sindiku et al (2015) PBB, PBDEs, TBP, TBBPA, TBPE Ultrasonic extraction reverse phase-high-performance liquid chromatography/UV detection (RP-HPLC/UV) Pöhlein et al (2005) DecaBDE, ethylene(bis-tetrabromophthal)imide (EBTBPI), DBDPE and TBBPA XRF screening followed by ion attachment mass spectrometry (IAMS) Sato et al (2010) TBBPA, PBDEs and HBCD XRF spectroscopic analysis at first followed by a surface wipe test or destructive chemical analysis gas detected. Despite the fact that this study was carried out only on a very small number of samples, there is a significant likelihood that WEEE has been used for the production of plastic FCMs.…”
Section: Introductionmentioning
confidence: 99%